Antenatal Clinic, a Missed Opportunity For Hypertension Education - Akaba, N.Y.O. (University of Ghana, 2015)
Hypertension in pregnancy is a leading cause of maternal morbidity and mortality. Mortality usually results from eclampsia, a condition which is heralded by specific prodromal signs. Eclampsia can easily be prevented if a patient recognizes these signs, and seeks prompt care. Antenatal care provides a good opportunity to educate clients on the prodromal signs.
Keywords: Antenatal; Clinic; Missed Opportunity; Hypertension Education